COMPARATIVE ANALYSIS OF SECTORAL INNOVATION SYSTEMS: RUSSIA AND BRAZIL ON THE REGIONAL JET MARKET - M. G. Yevtodyeva (Vestnik MGIMO-Universiteta)
The article investigates experience of the Brazilian aircraft maker Embraer and Russian aircraft companies UAC and Sukhoi Civil Aircraft (SCA) in development and sales of regional jets. Analysis of the Embraer’s ERJ-145 and E-Jet projects and the SCA-UAC ‘Sukhoi Superjet’ (SSJ-100) project is based on sectoral innovation approach which examines sectoral industrial development from the point of view of co-evolution of companies, technologies, demand dynamics and regulative norms and institutions as key elements of sectoral system of innovation (SSI). Revealing the most important features of evolution of the modern commercial aerospace sector such as high rate of innovation, R&D and subcontracting along the supply chain, development of new technologies, system-integration role of the leading global aircraft companies, outsourcing the production of major subsystems, liberalization of the regulative mechanisms and some others, the author demonstrates with the examples of the Brazilian and Russian cases how these changes were reflected in national sectoral systems of innovation of Brazil and Russia. The comparative research is based on such SSI parameters as efficiency of technological changes, accounting of changes in demand and in industry’s regulatory mechanisms, development of connections with suppliers, efficiency of investments, andorganization of sales. The research concludes that failures in realization of the SSJ-100 project were due less to negative consequences of the anti-Russian sanctions on aviation industry, than to some features of sectoral systems of innovation including those related to project management and mechanisms of funding. In contrast to the Embraer – a company that has managed to implement a state-of-the-art design and manufacturing system, achieved better balance between military and civil aircraft programs, successfully adopted foreign experience in coinvestment, risk-sharing partnerships and clusters, thus proving to be an effective system integrator, – the UAC and SCA achieved comparatively smaller progress in the above areas. Together with features of SSI other reasons of it include some mistakes of theSSJ-100 business strategy such as delays in design and certification processes, some technological imperfections of the airliner and therefore insufficient quantity of fixed supply arrangements with large foreign airlines, problems with investments, purchases of the equipment, deliveries of components and in other spheres of international cooperation, deficiencies of the after-sales service.